2022
DOI: 10.3389/fimmu.2022.863640
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immune-Inflammation Index Is Associated With Increased Urinary Albumin Excretion: A Population-Based Study

Abstract: BackgroundSystemic immune-inflammation index (SII) is a novel inflammatory marker, and inflammation has been reported to be related with renal damage. We aimed to investigate the possible relationship between SII and albuminuria.MethodsThe present cross-sectional study was conducted among adults with complete data about SII and urinary albumin-to-creatinine ratio (ACR) in 2005–2018 National Health and Nutrition Examination Survey (NHANES). SII was calculated as the platelet count × neutrophil count/lymphocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 51 publications
2
89
0
Order By: Relevance
“…The laboratory methodology of the complete blood count test is provided on the NHANES website ( 27 ). Moreover, plate count (PC), neutrophil count (NC), and lymphocyte count (LC) were measured in 1000 cells/μL, and the SII was calculated as PC * (NC/LC), according to previous studies ( 18 , 20 ). For a more comprehensive assessment of the association between SII and BMD, we similarly assessed the association of BMD and other inflammatory markers derived from PC, NC, and LC, including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), the product of platelet count and neutrophil count (PPN), PC, NC, and LC.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The laboratory methodology of the complete blood count test is provided on the NHANES website ( 27 ). Moreover, plate count (PC), neutrophil count (NC), and lymphocyte count (LC) were measured in 1000 cells/μL, and the SII was calculated as PC * (NC/LC), according to previous studies ( 18 , 20 ). For a more comprehensive assessment of the association between SII and BMD, we similarly assessed the association of BMD and other inflammatory markers derived from PC, NC, and LC, including platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), the product of platelet count and neutrophil count (PPN), PC, NC, and LC.…”
Section: Methodsmentioning
confidence: 99%
“…The systemic immune-inflammation index (SII) is a novel index based on the lymphocyte, neutrophil, and platelet counts. Accumulating evidence demonstrates that the SII is a useful index to reflect the systemic immune and infl ammatory status of the human body (17)(18)(19)(20). Moreover, previous studies have found that the SII has potential applications in disease risk and prognosis assessment (17)(18)(19)(20), especially in neoplastic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Low-grade inflammation is known to facilitate the development of hypertensive organ damage 14 . The systemic immune-inflammation index (SII) is a new inflammatory index based on circulating immune-inflammatory cells 15 . Therefore, we hypothesized that the SII could be a simple, economic, and feasible screening tool to predict the presence and severity of AOD.…”
Section: Introductionmentioning
confidence: 99%